Effects of lemon essential oil aroma on the learning behaviors of rats - Ogeturk, Murat; Kose, Evren; Sarsilmaz, Mustafa; Akpinar, Burhan; Kus, Ilter; Meydan, Sedat (Riyadh Armed Forces Hospital, 2010)
[Abstract Not Available]
Keywords: Persistent Painful Stimulation; Citrus Lemon; Female Rats